Directive Speech Acts Used by Teacher Via Zoom Cloud Meeting in English School Indonesia - Reni Febrianti; Fajri Usman; Sawirman Sawirman (RIRAI Publisher, 2022)
The purpose of this study is to categorize and describe the varieties, purposes, and tactics of teachers’ directive speech acts via zoom cloud meeting in English School Indonesia. This descriptive qualitative research used “teknik bebas libat cakap (SLBC)” technique or Uninvoled Conversation Observation Technique which is backed by the data collection techniques of keeping records and taking notes. This study makes use of Kreidler’s idea of directive speech act kinds (1998), Bach and Harnish’s (1979) theory of directive speech act functions and Yule’s (1990) theory of directive speech act strategy (1996). Data were analyzed using methodologies of referential and pragmatic distributional. The analysis of the data reveals that: (1) the types of directive speech acts used by teachers are commands, requests, and suggestions; (2) the functions of these speech acts are requestives, requirements, prohibitives, and advisories; and (3) the direct and indirect strategies employed by teachers are for directive speech acts. The type of command is the most dominant directive speech acts used by teachers(48%). With 40% incidence, the requirement function overtakes all other directive speech act functions. With 78% of teachers using it, the direct technique is the most common directive speech act strategy.